RELASI KUASA DESA WISATA BERKEMBANG DETUSOKO BARAT KABUPATEN ENDE NUSA TENGGARA TIMUR - Maximianus Ardon Bidi; Laila Kholid Alfridaus; Muhammad Adnan (Universitas Jenderal Ahmad Yani, 2023)
Development village tour is wrong one step strategic regarding _ activity social , cultural , and economy with utilise potency source owned power . _ Utilization potency tourist by no direct could create independence village with produce product and creation village for Fulfill his needs . So that for create a development process village optimal travel required strengthening of stakeholders in integration relation power , where each object power play role important To use support progress development based on approach with organization tourist and party related to the development process . This thing then Becomes ingredient study researcher about Relation Power Village Tour Develop West Detusoko , with results study showing that relation the power that happens in development process village tour showing existence integration dependency where for support the development process sector village tour _ besides fund a village with minimal resources help originated from formal institutions such as institutions in the area , other than that visible interaction _ in development process is powers that have interests. so that reference and recommendation researcher for support the development process is a development process village tour West Detusoko need role active Public with allotment development return to community , and need build network with source other self-help ( private ) for support accelerate the development process sector tourist West Detusoko.